Faktor Virulensi AvrBs3/PthA pada Ras III, Ras IV, Ras VIII, dan IXO93-068 Patogen Hawar Daun Bakteri (Xanthomonas oryzae pv. oryzae) - Dwinita W Utami; Triny S Kadir; Siti Yuriyah (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2011)
AvrBs3/PthA Virulence Factor of Bacterial Leaf BlightRace III, Race IV, Race VIII, and IXO93-068. Dwinita W.Utami, Triny S. Kadir, and Siti Yuriyah. Bacterial leafblight (BLB) is an important disease of rice and presentthroughout many of the rice-growing regions in the world,also in Indonesia. Xanthomonas oryzae pv. oryzae (Xoo) isthe causal agent and a member of the Protebacteria and likemany other this phyllum have a type III secretion system forprotein virulence effector (PVE) released on their pathogenicitysystem. Commonly, PVE in Xanthomonas sp., iscoded by AvrBs3/PthA family gene. This research wascoducted to identify the virulence factor of AvrBs3/PthA ondominant Indonesian BLB isolates (Race III, Race IV, RasVIII, and IXO93-068). This objective was obtained bysequence analysis through designed markers for membersof the virulence factor AvrBs3/PthA gene family (PthXo4,avrXa7#38, PthXoS and avrXa7sacB50). Results gave informationthat RaceIII is a dependent elicitor race due to noPVE transcript formed and intraceluler protein target withRLL type on NLS (nuclear localization signal). RaceIV andRaceVIII are the virulent race which PVE active formed withintraceluler protein target and have the RLL and RLLP typefor the NLS signal. While isolate IXO93-068 is a virulenisolate that active formed a PVE but the extraceluler proteintarget is due to no type of NLS. Based on cluster analysis,Race VIII has a genetic distance closely to PthXoS andavrXa7sacB50.